Effective Utilization of Pineapple Waste. Issue 1 (August 2021) - Madhumeena, S.; Preetha, R.; Prasad, Sandip
Abstract: India is the largest fruit and vegetable producer. Until fruit is eaten, fruit peel stays waste. Phenolic acids, ascorbic acid, β-carotenes, and flavonoids are the most bioactive components of pineapples. This is one of the secondary plant metabolites abundantly present in pineapple skins in this sample, ferulic acid. Ferulic acid is a low-toxic phenolic acid widely used in diet and cosmetics. Ferulic acid is extracted using different conventional and non-conventional methods such as Soxhlet extraction, Supercritical fluid extraction and Solvent extraction and the amount of ferulic acid is quantified using High performance liquid chromatography (HPLC). The study also evaluated the presence of total phenolic content (Gallic acid equivalent/GAE)and antioxidant activity. Soxhlet extraction using methanol and petroleum ether was the best solvent, methanol showed maximum ferulic acid concentration (0.7696 g/100g), phenolic content (2.365 mg g/GAE), antioxidant activity (45%) and percentage yield (90.5% mg). This study also analysed micronutrients such as vitamins (A, B, B1, B2, B6, B12 and C), calcium, potassium, phosphorus, iron, manganese, zinc and dietary fibre in the pineapple peel